Give us raw food materials: Qualitative analysis of stunting prevention challenges at Mandala Health Center - Suhartina Suhartina; Chris Cahyani Lase; Putranto Manalu; Buenita Sinurat (AcTion: Aceh Nutrition Journal, 2026)
Stunting remains a critical public health concern in Indonesia, with long-term implications for children's physical and cognitive development, despite governmental efforts that have failed to meet national targets. This study evaluated the effectiveness of the stunting prevention program at the Mandala Community Health Center in Medan and identified the supporting and inhibiting factors in its implementation. A qualitative case study was conducted from February to April 2025, gathering data through in-depth interviews, observations, and document analysis with five key informants, including health officials, community health cadres, and mothers. Edward III’s implementation theory (encompassing communication, resources, disposition, and bureaucratic structure) guided the analysis, with thematic patterns identified and validity ensured via triangulation and member checking. The results revealed effective program socialization across levels, adequate budget allocation offset by challenges from processed food assistance over raw materials, strong implementer commitment, and consistent adherence to standard operating procedures. The study concluded that the program was administratively robust, but reliance on processed food posed a key barrier, recommending policy shifts to prioritize raw food provision for greater effectiveness.